Performance analysis of hybrid stand-alone photovoltaic/fuel cell energy system [electronic resource] - Nasrin Sulaiman, 1980- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2010